SOCIO-ECONOMIC CONDITIONS OF MARINE FISHERMAN IN VISAKHAPATNAM DISTRICT OF ANDHRA PRADESH - Santha Kumari, Dr.R. (IJRDO - Journal of Social Science and Humanities Research, 2017)
Fish play a vital role in the food security of the country and the world as a whole fish is the major source of protein. Protein deficiency leads to chronic diseases like anemia which is dominant in developing countries like India. In addition to supplementation of protein, fish also supplies essential amino acids, fatty acids, water soluble and soluble vitamins. In other words fish meat is an essential component of human and animal nutrition. The demand of fish is continuously increasing based on the nutritional value and increasing population of the world and Food And Agricultural Organization( FAO) has estimated the demand for fish as 180 million tons by 2015 from the existing 145millionstons. Augmentation in fish production is possible by proper management of water bodies is the main concept of “BLUE REVOLUTION”